Does Monetary Compensation During Railway Construction Make Households Better-Off? - Janathin Saraswati; Dijan Rahajuni; Muhammad Farid Alfarisy (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2021)
The main aim of this study is to investigate the implication of overpass and double line railway construction conducted by PT Kereta Api Indonesia (KAI) on changes in income generating asset and the level of welfare in the community. We surveyed 28 households in Gambarsari Village, District Kebasen as affected communities who received monetary compensation from PT KAI. Comparisons between pre and post construction implication on the income generating asset of this group were made using Wilcoxon test. To compare whether the affected community become wealthier after receiving compensation, a ratio of per capita income to regional decent standard of living or Kualitas Hidup Layak (KHL) was used. The results of this study find that monetary compensation given by PT KAI has no significant impact on income generating asset. This result may be explained by the fact that instead of spending the received compensation on investment purposes such as buying a new land or kiosk, they use it for consumption purposes such as house makeover and renovation. Another important finding was that this study did not show any significant increase in household welfare level after the monetary compensation was given. A possible explanation to this result is the fact that most of affected household are elderly people who prefer to spend the compensated money for consumption rather than new income generating asset.Keywords: Impact evaluation, Overpass and Double Track Railway Construction, Land Acquisition.